Selective sulfate sorption from boric acid factory process liquor: Chitosan-bentonite biocomposite film synthesis as sorbent - Kaya, Fatih; Ozer, Ahmet (Pergamon-Elsevier Science Ltd, 2022)
Chitosan is a natural polymer that is renewable, biocompatible, and biodegradable. Bentonite is a natural mineral with low environmental effects. For this reason, chitosan- bentonite biocomposite film was synthesized as a sorbent and its characterized by FT-IR, SEM, EDX, CHNS elemental analysis and thermal analysis techniques. The sorbent was utilized for selective sulfate (SO42 ? ) sorption from boric acid factory process liquor, because one of the most important problems in the boric acid production process is sulfate impurity. The sulfate sorption capacity in the acidic region (pH < 5) was determined as 308.38 mg/g and the equilibrium time was determined as 10 min. It has also been found that the sorbent is regenerative and reusable. Sulfate sorption took place by means of primary amine (-NH2) groups in the structure of the biocomposite. In addition, it was considered that the synthesized sorbent acts as a weakly basic anion exchanger resin. It was determined that the total sulfate salt concentration in the process liquor medium decreased by approximately 30.36% depending on the sulfate sorption. In this context, it is considered that the boric acid factory process liquor has been successfully purified.
Keywords: Chitosan-bentonite biocomposite film; Modified chitosan; Selective sulfate sorption; Ion exchange; Boric acid purification process; Impurity control